Peran Teknologi dalam Meningkatkan Motivasi Belajar Siswa - Khairo, Nadia Tul; Hairani, Esi (Indonesian Journal of Teaching and Teacher Education, 2024)
The purpose of this study was to find out information or analyze the role of digital technology in increasing student motivation. Digital technology is an important tool in the learning process in the era of the industrial revolution 4.0 so that in all domains it is expected to be able to apply it, including the field of education, which in fact is students who study three years in school who are the successors of the next generation who are required to be able to compete in technological developments. This study uses a qualitative method with a case study approach using purposive techniques and snowball sampling to obtain data from resource persons at the State Vocational High School 1 Simpang Kiri Subulussalam City majoring in Multimedia. Furthermore, the findings or results in research that the role of digital technology in the multimedia department is able to provide learning motivation for students to be able to create innovative and creative works so that with the application of digital technology in learners can produce productive students. However, facilities such as computers in schools are not adequate or not enough to meet computer-based education standards, which are still minimal. So, it is hoped that for the next generation the computer facilities have been fulfilled in order to create effective learning.